2021
DOI: 10.1016/j.celrep.2021.108934
|View full text |Cite
|
Sign up to set email alerts
|

Slower prefrontal metastable dynamics during deliberation predicts error trials in a distance discrimination task

Abstract: Highlights d Prefrontal activity in monkeys performing a distance discrimination task is metastable d Duration of metastable states is longer before errors d Latency of state transition is longer in correct difficult trials d States may code for relative distance based on stimulus features or presentation order

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“… 8 More recently, states coding for more abstract stimulus features have been found in a distance-discrimination task in which monkeys had to report which of two stimuli were farther from a central location on a computer screen. 9 In this case, it was found that some states reflect the relative distance of the two stimuli based on their features [e.g., whether they were a blue circle or a red square, see Fig. 3(a) ].…”
Section: Metastable Dynamics In Neural Circuitsmentioning
confidence: 97%
See 4 more Smart Citations
“… 8 More recently, states coding for more abstract stimulus features have been found in a distance-discrimination task in which monkeys had to report which of two stimuli were farther from a central location on a computer screen. 9 In this case, it was found that some states reflect the relative distance of the two stimuli based on their features [e.g., whether they were a blue circle or a red square, see Fig. 3(a) ].…”
Section: Metastable Dynamics In Neural Circuitsmentioning
confidence: 97%
“…Since these original works, metastable dynamics has been reported in rat gustatory cortex (GC), 12 in monkey somatosensory, motor, and premotor cortex, 7,15,53 in monkey's area V4, 54 in monkey's orbitofrontal, 14 parietal 13 and dorsolateral prefrontal cortex, 9 in the hippocampus of rats, 55 in the zebrafish 56 and in multiple human brain areas. 6 …”
Section: Metastable Dynamics In Neural Circuitsmentioning
confidence: 99%
See 3 more Smart Citations